1937. A Dedicated OPAT Program Reduces Readmission and Complications Rates. (26th November 2018) - Willeford, Wesley; Carr, J Andrew; Lee, Rachael A; Patel, Mukesh; Heath, Sonya; Baddley, John W; McCarty, Todd P
Abstract: Background: Outpatient Parenteral Antibiotic Therapy (OPAT) programs provide patients with infections an alternative to prolonged hospitalization. Despite the benefits of decreased hospital lengths of stay (LOS), risks related to central venous catheter (CVC)-related complications and medication toxicities remain. We implemented intensive monitoring with our antimicrobial stewardship program (ASP) aimed at decreasing the frequency of complications and readmissions. Methods: A retrospective study was conducted including all patients discharged from the Birmingham Veterans Affairs (VA) Medical Center on OPAT from January 1, 2014 to December 31, 2014 (Period 1) and January 1, 2015 to December 31, 2016 (Period 2). Prior to January 1, 2015 OPAT was managed by individual infectious diseases physicians. Starting with Period 2, OPAT was monitored by a dedicated ASP physician and pharmacist. Episodes that eclipsed both periods were excluded. Data collection included demographics, antibiotic indication, treatment received, and clinical outcomes (frequency and types of drug-related complications, acute kidney injury [AKI] defined as a rise in serum creatinine requiring a change in antibiotic dosing, CVC complications, hospital readmission, and planned OPAT duration [difference between discharge and planned stop dates]). Results: Period 1 included 120 patients, period 2 included 299 patients. The mean planned OPAT duration was 30.3 days in Period 1vs. 28.3 days in Period 2 ( P = 0.21). Demographics and OPAT indications for each period are in Table 1. Fewer patients had complications in Period 2 compared with Period 1 (50 [42%] vs. 77 [26%], P = 0.001). Complications for each period are detailed in Table 2. Readmission rates were lower in Period 2 compared with Period 1 (27.5% of patients vs. 10%, P < 0.0001). Year is significantly negatively associated with complications ( P < 0.0001) and hospitalization ( P < 0.0001), Figure 3. Conclusion: The establishment of an OPAT-ASP tasked with close monitoring of therapy improved patient outcomes with reductions in the rate of complications and readmissions in our VA population. Our data support the center's efforts to dedicate centralized resources to improving the outcomes of OPAT patients. Disclosures: All authors: No reported disclosures.